Retorika Dakwah Dalam Perspektif Tafsir Al-Qurâ€™an - M. Alaika Nashrulloh (IAI Darussalam, 2016)
Al-Qurâ€™an which incidentally is the guide covers all aspects of human life, including communications, propaganda, and rhetoric. In propaganda, communication is one important factor in order to achieve the goal. While in the communication process known the science of rhetoric is the art of speaking. Therefore in this article will be discussed from the perspective of propaganda rhetoric interpretation of the Koran. The analytical methods used in discussing this theme is a descriptive-analytical method of data collection muqari interpretation or comparison, as well as collaborate with the tahlily method. The findings, obtained after the discussion is that in the Qur'an, there are 11 verses relating to the rhetoric of propaganda, which can be classified into six categories, namely: â€ Ù‚ÙˆÙ„ Ù…Ø¹Ø±ÙˆÙ (speech good / good verbal), â€ Ù‚ÙˆÙ„ Ø³Ø¯ÙŠØ¯ (the correct word / right verbal), â€ Ù‚ÙˆÙ„ Ø¨Ù„ÙŠØº (words that trace / influential verbal), â€ Ù‚ÙˆÙ„ Ù…ÙŠØ³ÙˆØ±(words appropriate / reasonable verbal), Lafadz â€ Ù‚ÙˆÙ„ Ù„ÙŠÙ† (words gentle / bland verbal) Lafadz â€ Ù‚ÙˆÙ„ ÙƒØ±ÙŠÙ… (words noble/Excellency verbal) , The sixth category of those words will be very effective when used by the communicant and communicator for the appropriate circumstances.